Sinval Garcia: um artista contemporâneo na confluência entre linguagens - NASCIMENTO, Cinthya Marques do (Universidade Federal do Pará, 2018)
The current research discourses part of the Sinval Garcia’s work (1966 - 2011) which performs major production in the Brazilian’s visual arts field. In his production, we will focus on the exhibition “Samsara” (1997) “Paisagens In-visíveis” (In-visible Landscapes) (2005) and “A Câmara da Transmutação Secreta” (The House of Secret Transmutation) (2009). This cut of his work constitutes by the interstices between photography and other languages, and it will be focused particularly on the established relationship with painting, observed over the links between the works within the artist's production context. To do this we used the concepts of phenomenology M.Merleau-Ponty, the study Laura Gonzalez Flores on photography and painting, beyond thought of Flusser about a philosophy for photography. This research contribute to the discussions of a story of contemporary photography in Pará and Brazil, and contribute to the reflective and critical stance of contemporary art nationwide.